(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2014)
Introduction: Delayed reverse from the effect of neuromuscular blockade and from the effect of anaesthesia is a concern among anaesthesiologists. Objectives: Objectives of the study were to compare reversal pattern of neuromuscular blockade by clinical and instrumental methods and to elicit reliable clinical parameters. Methods: This prospective study was carried out in CMH, Dhaka among 50 adult patients and reversal pattern of neuromuscular blockade was evaluated by clinical and instrumental methods among pancuronium group(Group-I) and rocuronium group(Group-II). All data were collected in data collection sheet and were compiled and analyzed by Studentst test. Results: Clinical assessment was carried out by bedside test for muscular function & instrumental assessment was carried out by nerve stimulator and Train of Four (TOF). In pancuronium group (Gp-I) clinically patient was reversed on average (6.19 ± 2.04 min) (mean±SD, n=25) earlier than instrumental method of which tidal volume was found less reliable. But in rocuronium group (Gp-II) instrumentally patient was reversed average (12.56 ± 3.41 min) (mean±SD, n=25) earlier than clinical method of assessing reversal, here also tidal volume was found less reliable among clinical variables. Conclusion: The study revealed that tidal volume is the less reliable among the clinical variables. In Group-I clinical reversal criteria for neuromuscular blockade were fulfilled earlier than that of instrumental method but in Group-II instrumental criteria were fulfilled earlier than clinical method. We should combine 2 or 3 clinical criteria for adequate reversal from neuromuscular blockade. DOI: http://dx.doi.org/10.3329/jafmc.v9i1.18725 Journal of Armed Forces Medical College Bangladesh Vol.9(1) 2013: 43-48